STRATEGI PENGEMBANGAN DESA MANTAR SEBAGAI KAWASAN DESA WISATA DI KABUPATEN SUMBAWA BARAT - Zaenafi Ariani, Muhammad Nursan (Universitas Mataram, 2017)
ABSTRACTMantar Village is a village that is designated as a tourist area by the West Sumbawa Regency Government. Although already established as a tourist village, Mantar Village management as a tourist village is still not maximized. Therefore, the purpose of this study is to determine the main types of tourism and support and determine the strategy of tourism development in MantarVillage. The method used in this research is descriptive research method. Data were collected using survey technique to 40 respondents chosen by purposive sampling. AHP analysis was used to determine the main types of tourism and supporters, and to determine the development strategy Mantar Village tourism was used SWOT analysis. The results of the study using AHP analysis indicate that the main tourism in Mantar Village based on the criteria of stakeholder support, facilities and infrastructures, and the main tourist attraction in Mantar Village is Nature Tourism (0.3012) and Paragliding Sports Tour (0.2860) and historical and cultural tourism (0.2134 ) and agricultural tourism (0.1994) are support tours. Mantar Village development strategy as a tourist village in West Sumbawa Regency based on SWOT analysis is a S-O (Strenght-opportunity) strategy that is a strategy that utilizes the power it possesses to seize the opportunity or aggressive strategy. Priority of strategy that need to be done is to arrange Mantar Village tour package and increase cooperation with private party, increase promotion of tourist village, quantity and quality of tourism management HR, supporting facilities and infrastructure, planning development and management of tourist village,socialization in order to increase community awareness related tourist villageKeywords: Development Strategy, AHP, SWOT, Tourism, Mantar Village